PERSEPSI ANGGOTA CLUB MOTOR TERHADAP GAYA HIDUP KOMUNITAS DI SURABAYA - Nurbaity, Fitri; Bungin, Burhan; Satvikadewi, AAI Prihandari (representamen, 2016)
This research is motivated as a means of transportation that is integral lifestylefor society. As well as Motor Gede become the image of it’s owner, become a hobby forthe owner, and in this case the owner or user of the big motorcycle start looking for acontainer or a place to channel his hobby which later formed the club MoGe. This studyaims to determine the perceptions of the lifestyle community in the march MoGe. Theoryused is the theory S-O-R is a reaction that is spesific to spesific stimuli so that one canexpect and compatibility between the message and the reaction communicant. Researchfound that club motor gede classified as fancy or high class club as a lifestyle and it’smembers have the perceptions that the club motor gede must have solidarity and highloyalty to fellow members.Keywords: PERCEPTION, LIFESTYLE, CLUB MOGE